Hypersensitivity Responses in the Central Nervous System - Khorooshi, Reza; Asgari, Nasrin; Mørch, Marlene Thorsen; Berg, Carsten Tue; Owens, Trevor (Frontiers in Immunology, 2015)
Immune-mediated tissue damage or hypersensitivity can be mediated by autospecific IgG antibodies. Pathology results from activation of complement, and antibody-dependent cellular cytotoxicity (ADCC), mediated by inflammatory effector leukocytes include macrophages, natural killer cells (NK) cells and granulocytes. Antibodies and complement have been associated to demyelinating pathology in multiple sclerosis (MS) lesions, where macrophages predominate amongst infiltrating myeloid cells. Serum-derived autoantibodies with predominant specificity for the astrocyte water channel aquaporin-4 (AQP4) are implicated as inducers of pathology in neuromyelitis optica (NMO), a CNS demyelinating disease where activated neutrophils infiltrate, unlike in MS. The most widely-used model for MS, experimental autoimmune encephalomyelitis (EAE), is an autoantigen-immunized disease that can be transferred to naive animals with CD4+ T cells, but not with antibodies. By contrast NMO-like astrocyte and myelin pathology can be transferred to mice with AQP4-IgG from NMO patients. This is dependent on complement, and does not require T cells. Consistent with clinical observations that interferon-beta is ineffective as a therapy for NMO, NMO-like pathology is significantly reduced in mice lacking the Type I IFN receptor. In MS there is evidence for intrathecal synthesis of antibodies as well as blood-brain barrier (BBB) breakdown, whereas in NMO, IgG accesses the CNS from blood. Transfer models involve either direct injection of antibody and complement to the CNS, or experimental manipulations to induce BBB breakdown. We here review studies in MS and NMO that elucidate roles for IgG and complement in the induction of BBB breakdown, astrocytopathy and demyelinating pathology. These studies point to significance of T-independent effector mechanisms in neuroinflammation.